Are Bad Institutions Always Bad for Society? Trust and Cooperation in Times of Crisis - Pierluigi Conzo; Gianmarco Daniele; Andrea F.M. Martinangeli; Willem Sas (CESifo GmbH, 2025)
This paper investigates how institutional and social trust respond to crisis situations, and to what extent different kinds of trust interact in such a context. In an online survey experiment on 4,400 representative respondents from Italy, participants are exposed to a real-world flooding scenario and randomly assigned to information treatments portraying institutions as effective, ineffective, or neither of the two. When institutions are framed as effective, institutional trust and donations to a grassroots environmental NGO increase, while social trust and cooperation norms remain stable. When institutions are seen as unprepared, participants do not compensate by trusting others or stressing cooperation. Instead, they increase support for the NGO as well, suggesting crisis management delegation to motivated and organised citizens. When no information is provided about institutional quality all trust indicators rise, albeit more noisily. These findings suggest delegation as a distinct response to institutional failure and point to the need to study trust in civic movements as an intermediate form between institutional and interpersonal trust.
Keywords: D91; H84; Z13; C93; D83; H11; P16; 330; social trust; institutional trust; external shocks; online survey experiment; climate change; cooperation; grassroot movements; delegation